Some New Equipments for Improved Nursery Practices - Gera, Mohit; Gera, Neelu; Bhandari, A. S. (Indian Forester, 1996)
In wake of increasing emphasis on Tree improvement and production forestry, attempts have been made to aid the field foresters, private planters and nurserymen with improved techniques, tools and equipments for enhancing the quality of planting stock. The article also aims at offering cost effective technology to user agencies for vegetative multiplication of selected material by employing the modern methods of mist propagation and shade house systems.